Visual perception and logical thinking in children of five years at educational institution - Fajardo Alejos, Melissa (2019)
The research aimed to establish whether there was a relationship between visual perception and logical thinking in children of 5 years of an Educational Institution. It was carried out from the quantitative approach, non-experimental design, correlational level and cross section. The sample was 80 students from the 5-year classrooms of an educational institution in San Martín de Porres (S.M.P). For the data collection, the Frostig Test (1963) and the pre-calculus test of Milicic and Schmidt (1995) were applied. The results obtained showed that visual perception has a high (0.750) and significant (p <0.01) correlation with logical thinking in an educational institution of S.M.P. Therefore, it was found that there is a high and significant relationship between visual perception and logical thinking in children of 5 years of an educational institution.